The Influence of Supportive Interventions On Decision Self-Efficacy and Decision Conflict in Mothers with Previous Cesarean Section to Choose Mode of Delivery: A Randomized Clinical Trial - Roghayeh Pakdaman; Mahboobeh Firoozi; Mansoureh Mirzadeh; Kataneh Kazemi; Jamshid Jamali (Mashhad University of Medical Sciences, 2022)
Background & aim: Vaginal birth after cesarean section is a strategy which is recommended to reduce repeat cesarean section. Concerns about its complications can cause crisis in decision making. Therefore, this study was performed to investigate the effect of supportive interventions on decision self-efficacy and decision conflict in mothers with previous cesarean section to choose mode of delivery.Methods: This randomized clinical trial was carried out on 60 pregnant women with a history of previous cesarean section and gestational age of 28-30 weeks, who referred to the health centers in Bojnourd, Iran in 2020. The participants were randomly divided to intervention and control groups. Supportive interventions in the intervention group included in-person supportive counseling approach via three 45-minutes sessions per week, telegram channel, educational pamphlet and telephone. Data was collected in both groups before and four weeks after intervention by valid and reliabe decision self-efficacy and decision conflict questionnaires. The analysis of data was done by SPSS software (version 25) using independent t-test, paired t-test and Mann-Whitney.Results: There was a statistically significant difference in mean scores of decision self-efficacy (P =0.005) and decision conflict (P=0.010) in the intervention group four weeks after supportive interventions. While, the difference in mean scores of these variables was not significant in the control group.Conclusion: Supportive interventions could help to improve the decision self-efficacy and decrease decision conflicts in mothers with previous cesarean section to choose vaginal birth after cesarean section. It can be recommended as an effective strategy to promote natural birth.